The behavioural ecology of parasites - Lewis, E. E.; Campbell, J. F.; Campbell, J. F.; Lewis, E. E.; Sukhdeo, M. V. K.; Sukhdeo, M. V. K. (Wallingford :CABI Publishing, 2002)
This book addresses the behavioural adaptations of parasites across a broad range of taxa, including parasitoid wasps, entomopathogenic nematodes, seed-feeding insects and plant-parasitic nematodes. The chapters emphasize the fundamental principles of parasitism and address the diversity and sophistication of parasite behavioural adaptations. The chapters are arranged in 4 sections discussing foraging for hosts, host infection, interactions among parasites within hosts and parasite-host interactions.
Keywords: FF620 - Plant Pests, (New March 2000); LL822 - Protozoan, Helminth, Mollusc and Arthropod Parasites of Animals, (New March 2000); VV220 - Protozoan, Helminth and Arthropod Parasites of Humans, (New March 2000); YY500 - Behaviour (Wild Animals), (New March 2000); YY700 - Pathogens, Parasites and Infectious Diseases (Wild Animals), (New March 2000); ZZ396 - Microbial Life Cycles, (New March 2000)